Root carbon estimation in forests of the Sierra de Manantlán, México - Quintero-Gradilla, Shatya D.; Muñoz, Antonio; Castillo-Parra, Víctor M. (Instituto de Ecología, A.C., 2022)
Belowground carbon estimation is essential for understanding carbon dynamics in forests. Root carbon was quantified in a pine forest (PF) and a tropical montane cloud forest (TMCF) in the Sierra de Manantlán, México. Soil samples were taken at a depth of 30 cm, and roots were extracted and classified into fine (<2 mm) and coarse (> 2 mm) roots. Soil bulk density and soil moisture were determined as well. A Student's t-test was used for statistical analysis with a significance level of p < 0.05. In the PF, the carbon stored in roots was 3.51 Mg ha-1 ± 0.92 Mg ha-1, significantly lower than in the TMCF with 4.98 Mg ha-1 ± 1.29 Mg ha-1. The ratio of C stored between fine and coarse roots was 0.86 and 0.78 for PF and TMCF, respectively. No significant differences were observed in the C stored in the fine roots between both forests; for the coarse roots, the C content was higher in the TMCF. The soil bulk density and soil moisture in the PF were 0.73 g cm-3 and 23.42%, respectively. Likewise, these variables for the TMCF were 0.59 g cm-3 and 29.93%. With these data, a better understanding of the distribution of carbon in roots for different vegetation types was obtained.